Implementation of EKF based sensorless drive system using vector controlled PMSM fed by a matrix converter - Aydogmus, O.; Sunter, S. (Elsevier Sci Ltd, 2012)
A PMSM sensorless drive fed by a matrix converter has been designed to show that a drive system with high performance and efficiency can be constructed by combining the advantages of matrix converters, permanent magnet synchronous motors and sensorless control. Sensorless control of the motor is performed by using Extended Kalman Filter. The characteristics of matrix converter and performance of PMSM which are implemented by using a digital signal controller has been analyzed. Differences between the sensored and sensorless PMSM drive systems are also presented by considering the waveforms of the drive system. Promising results illustrated that EKF based sensorless control of matrix converter fed PMSM drive system with a good performance is achievable at medium and high speed operations. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Digital signal controller; Kalman filtering; Matrix converter; Permanent magnet synchronous motor; Vector control